Associations of gender and age groups on the knowledge and use of drug information resources by American pharmacists - Carvajal MJ; Clauson KA; Gershman J; Polen HH (Centro de Investigaciones y Publicaciones Farmaceuticas, 2013)
Objectives: To explore knowledge and use of drug information resources by pharmacists and identify patterns influenced by gender and age-group classification. Methods: A survey questionnaire was mailed nationwide to 1,000 practitioners working in community (n = 500) and hospital (n = 500) settings who answer drug information questions as part of their expected job responsibilities. Responses pertaining to drug information resource use and knowledge of different types of drug-related queries, resource media preferences, and perceived adequacy of resources maintained in the pharmacy were analyzed by gender and age group. The t statistic was used to test for significant differences of means and percentages between genders and between age groups. Descriptive statistics were used to characterize other findings.Results: Gender and age group classification influenced patterns of knowledge and use of drug information resources by pharmacists. They also affected pharmacists' perceptions of the most common types of questions prompting them to consult a drug information reference, as well as the resources consulted. Micromedex, exclusively available in electronic format, was the most commonly consulted resource overall by pharmacists. Lexi-Comp Online was the leading choice by women, preferred over Micromedex, but was not one of the top two resources selected by men. Conclusion: This study successfully identified the influence of gender and age-group classification in assessing drug information resource knowledge and use of general and specific types of drug-related queries.